Hidrops pri keratokonusu - primer treh bolnikov - Pečjak, Urša (Zdravniški vestnik, 2010)
Keratoconus is a bilateral, non-inflammatory and progressive corneal ectasia. It is diagnosed more often in people with Down syndrome. Acute hydrops occurs in 3 % of patients with keratoconus. There is an influx of aqueous into the cornea as a result of a rupture in Descemetćs membrane. It can cause a sudden decrease in vision, pain, red eye, photophobia and profuse tearing. Therapy ofhydrops is symptomatic. Corneal oedema usually resolves in several weeks or months. With accurate and prompt clinical diagnosis hospitalisation of patients with acute hydrops is unnecessary, as we assume it doesnćt shorten the healing period or affect the functional outcome. Close observation allows for the early detection and treatment of complications such as perforation andinfection.
Keywords: Adult; akutni hidrops; Corneal Edema; Diagnosis; Down Syndrome; Downov sindrom; Keratoconus; keratokonus; Keratokunus; Odrasli; oftalmologija; roženica; Roženica, edem; Therapy; zdravljenje